Concepts, Applications and Emerging Opportunities in Industrial Engineering - Moynihan, Gary (IntechOpen, 2021)
From their initial focus in manufacturing, the industrial engineering principles, tools, and techniques have spread across a spectrum of application areas. Topics covered in this book apply to this continuum of application, including operations planning, safety, quality, production control, inventory management, operations research, supply chain management, and continuous improvement. This edited book comes at an opportune time. It incorporates new knowledge and expertise in a rapidly changing engineering discipline that is a vital force in a wide range of manufacturing, service, educational, and government organizations. Such concepts as lean systems, sustainability, systems thinking, data analytics, and additive manufacturing, as well as utilization of advanced computer software, have further expanded industrial engineering's breadth. Each chapter reflects important aspects of these advances.